The effects of cook-top temperature on range hood capture efficiency. (29th October 2020) - Meleika, Sammy; Pate, Michael
Abstract : In this study a test procedure for determining capture efficiency (CE) of wall-mounted range hoods, namely ASTM-E3087.18, was used to investigate how the temperature of the simulated cook-top influences CE. ASTM-E3087.18 was initially released in 2017 and revised within one year to modify the temperature requirements of the cook-top from 200 °C to 160 °C; however, there is no evidence of a detailed study being performed to quantify the effects of this temperature change on CE. The study reported herein performed testing at 200 °C, 160 °C and 130 °C for five range hoods with three different design types. CE ranged from 60.3–92.9%CE with CE variations as high as 9.2%CE when varying temperature, and uncertainty (δ) always varying by less than 1.0%CE. The influence of cook-top temperature on CE repeatability, reproducibility and variability was also investigated, with each metric varying by a maximum of 1.2%CE, 1.5%CE and 1.1%, respectively, with varying temperatures. Range hoods with poor burner coverage (i.e. over-the-range microwaves) showed higher variability/uncertainty, indicating temperature effects are more dominant when range hoods have less burner coverage. It is possible that future HVI/ASHRAE certifications specify different acceptability/test requirements for CE, as well as the CE uncertainty/repeatability, of range hoods with poor burner coverage.